Process Optimization for Madhuca indica Seed Kernel Oil Extraction and Evaluation of its Potential for Biodiesel Production - S. Sudalai, S. Prabakaran, M. G. Devanesan and A. Arumugam (Nature Environment and Pollution Technology)
The current research aims to optimize the solvent-based oil extraction process from Mahua (Madhuca indica) seed using response surface methodology and biodiesel production using heterogeneous catalysts. The oil extraction was varied through the levels of process parameters including extraction temperature (60 to 80°C), solvent-to-seed ratio (3 to 9 wt/wt), and time (2 to 4 h). The experiments were designed following the Central Composite model. The regression model provided optimal values for the selected process parameters based on the extraction yield percentage. To ensure the model’s reliability, it was experimentally validated. Maximum experimental oil yields of 50.9% were obtained at an optimized extraction scenario of 70 °C extraction temperature, solvent-to-seed ratio of 6 wt/wt, and time 4 h. The extracted oil’s physicochemical properties and fatty acid composition were tested. Also, using copper-coated dolomite as a catalyst, the extracted oil was transformed into biodiesel via transesterification. The FAME (94.31%) content of the prepared biodiesel was determined via gas chromatography. As a result, the findings of this study will be useful in further research into the use of Madhuca indica as a potential feedstock for biodiesel production.